Towards a pragmatic analysis of modals "shall" and "will" in Chaucer's language - Nakayasu, Minako (Adam Mickiewicz University, 2010)
This paper attempts to provide the first systematic analysis of the modals SHALL and WILL in Chaucer’s language from pragmatic viewpoints. In addition to speech acts and alternation in discourse, this study examined modality in detail, which has a close relationship to pragmatic factors. Whereas SHALL is distributed across all kind of modalities, WILL has a limited variety, with a strong preference to dynamic modality. The inventory of speech acts suggests a strong connection to relevant modality, although some cases are not related to any particular modality. WILL again has a more limited variety than SHALL. Incorporating these results into analysis, the scope of examination is extended to the alternation in discourse, i.e., discourse markers, successive employments of the same modal, and alternative uses of both modals. The findings here which other studies would ascribe simply to a matter of variation are in fact well-motivated and controlled by various factors such as modality, speaker-based vs. hearer-based speech acts, and social role. It is suggested that further analysis of discourse and modals in other periods will shed more light on the pragmatic development of the modal and temporal systems in English.